Poet, Teacher, Acadie: Using Poetic Inquiry as a Tool for Unearthing Identity - Vincent, Adam (Journal of the Canadian Association for Curriculum Studies, 2020)
Uncovering an authentic version of self-identity is at once difficult and profound. Our self-identity affects how we (re)present ourselves to the outside world and ultimately how we engage as educators. Through more than twenty years of writing experience, and a decade as an educator at the post-secondary level, I have learned that poetry has power. However, it is only recently that I have come to further appreciate its power to explore the links between place and self-identity (Vincent, 2020). Poetry offers a chance to dwell in the depths of self-identity while simultaneously tapping into the liminal spaces that often unconsciously frame who we are. This presentation focuses on my on-going journey of self-discovery as an Acadian Canadian, and explores how poetry, as a tool for textual analysis and self-analysis, has helped me to unearth previously unexamined parts of my identity. This presentation also includes demonstrations of ways that other educators, whether experienced in poetry or not, can use poetry and/or poetic techniques to begin to explore their own identities as educators.